PERFIL SÓCIODEMOGRAFICO E ECONÔMICO DE PACIENTES EM TRATAMENTO ONCOLÓGICO - Oliveira, Daiane d.; Lauter, Dagmar S.; Rosanelli, Cleci L. S. P.; Kolankiewicz, Adriane C. B.; Loro, Marli M.; Gomes, Joseila S. (Salão do Conhecimento, 2013)
Resumo